Pushing forward: exploring the impact of the sitting position on muscle activation patterns and force generation during paralympic sit-cross-country skiing - Leonie Hirsch; Hatim Barioudi; Dominic Wintergerst; Ralf Rombach; Walter Rapp; Thomas Felderhoff; Natalie Mrachacz-Kersting; Natalie Mrachacz-Kersting (Frontiers Media S.A., 2024)
Paralympic cross-country sit-skiing is a discipline of the Paralympic Winter Games where athletes use a specialized sledge. Athletes are classified into different groups according to their functional abilities. The double poling technique is used to push the sledge forward and generate speed. Different sitting positions in the sledge are used based on the individual impairment. To date there is no data available on the effects of these different positions on muscle activation patterns. The aim of this study was to analyze the muscle activation patterns of the trunk and upper body muscles in relation to the poling force. Nine Able-bodied athletes were tested on a treadmill at submaximal speed in three sitting positions for 4 min in a flat and uphill condition. Sitting positions included a "knee-high" position, a "knee-low" position, and a "neutral" position with the sitting platform parallel to the ground. Unilateral pole forces and surface EMG from three trunk muscles, two upper limb muscles, and one lower limb muscle were recorded simultaneously on the dominate side. Data were segmented into individual cycles and mean values and standard deviations calculated for each subject and condition. Statistical analyses, including a Friedman test and Bonferroni correction, were applied to examine significant differences across different sitting positions. Our findings demonstrate that while certain muscle groups such as the erector spinae and triceps show consistent patterns of activation across different sitting positions, there is considerable variability among individual athletes, suggesting individualized strategies for task execution. Overall, force application was most efficient in the "knee low" position with 691.33 ± 148.83 N and least efficient in the "knee high" position with 582.81 ± 115.11 N. Testing impaired athletes will be the next step in understanding the neurophysiological aspects of the poling movement. This experimental protocol provides a basis for understanding the movement of paralympic cross-country sit-skiing in greater depth.